A member of the TERMINAL FLOWER1/CENTRORADIALIS gene family controls sprout growth in potato tubers - Morris,WL; Alamar,MC; Lopez-Cobollo,RM; Castillo,JC; Bennett,M; Van,der Kaay J; Stevens,J; Kumar,Sharma S; McLean,K; Thompson,AJ; Terry,LA; Turnbull,CGN; et al. (Journal of Experimental Botany, 2019)
Potato tuber bud dormancy break followed by premature sprouting is a major commercial problem which results in quality losses and decreased tuber marketability. An approach to controlling premature tuber sprouting is to develop potato cultivars with a longer dormancy period and/or reduced rate of sprout growth. Our recent studies using a potato diploid population have identified several QTLs that are associated with tuber sprout growth. In the current study we aim to characterise a candidate gene associated with one of the largest effect QTL for rapid tuber sprout growth on potato chromosome 3. Underlying this QTL is a gene encoding a TERMINAL FLOWER 1/ CENTRORADIALIS homologue (PGSC0003DMG400014322). Here we use a transgenic approach to manipulate the expression level of the CEN family member in a potato tetraploid genotype (cv. Désirée). We demonstrate a clear effect of StCEN expression manipulation, with decreased expression levels associated with an increased rate of sprout growth, and over-expressing lines showing a lower rate of sprout growth than controls. Associated with different levels of StCEN expression were different levels of ABA and cytokinins implying a role in controlling the levels of plant growth regulators in the apical meristem.